Impaired Wheel Running Exercise in CLC-1 Chloride Channel-Deficient Myotonic Mice - Van Lunteren, Erik; Moyer, Michelle; Cooperrider, Jessica; Pollarine, Jennifer (Frontiers in Physiology, 2011)
Background: Genetic deficiency of the muscle CLC-1 chloride channel leads to myotonia, which is manifested most prominently by slowing of muscle relaxation. Humans experience this as muscle stiffness upon initiation of contraction, although this can be overcome with repeated efforts (the “warm-up” phenomenon). The extent to which CLC-1 deficiency impairs exercise activity is controversial. We hypothesized that skeletal muscle CLC-1 chloride channel deficiency leads to severe reductions in spontaneous exercise. Methodology/Principal Findings: To examine this quantitatively, myotonic CLC-1 deficient mice were provided access to running wheels, and their spontaneous running activity was quantified subsequently. Differences between myotonic and normal mice in running were not present soon after introduction to the running wheels, but were fully established during week 2. During the eighth week, myotonic mice were running significantly less than normal mice (322 ± 177 vs 5058 ± 1253 meters/day, P = 0.025). Furthermore, there were considerable reductions in consecutive running times (18.8 ± 1.5 vs 59.0 ± 3.7 minutes, P < 0.001) and in the distance per consecutive running period (58 ± 38 vs 601 ± 174 meters, P = 0.048) in myotonic compared with normal animals. Conclusions/Significance: These findings indicate that CLC-1 chloride deficient myotonia in mice markedly impairs spontaneous exercise activity, with reductions in both total distance and consecutive running times.